2014
DOI: 10.2478/10004-1254-65-2014-2398
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of hepatocyte pretreatment with coenzyme Q10 against statin toxicity

Abstract: Statins are potent cholesterol-lowering drugs that can have serious adverse effects on the muscles and liver. The aim of our in vitro study was to establish the protective effect of coenzyme Q 10 (CoQ 10 , in its optimal dose of 200 µmol L -1 ) against cytotoxicity induced by atorvastatin, simvastatin, and lovastatin in isolated rat hepatocytes by observing parameters such as cell death, reactive oxygen species formation, lipid peroxidation, mitochondrial membrane potential, and cellular reduced and oxidised g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
2
12
0
4
Order By: Relevance
“…We also saw that pretreatment with CoQ10 could block the release of Cyt c, inhibit the activation of caspase-3 and caspase-9, and regulate the expression of Bcl-2/Bax to reach equilibrium and prevent subsequent apoptosis in L-02 hepatocytes. These results are compatible with the findings of other studies using CoQ10 against iron-induced neuronal toxicity [28], statin toxicity in hepatocytes [50], or ethanol-induced apoptosis in corneal fibroblasts [51]. …”
Section: Discussionsupporting
confidence: 92%
“…We also saw that pretreatment with CoQ10 could block the release of Cyt c, inhibit the activation of caspase-3 and caspase-9, and regulate the expression of Bcl-2/Bax to reach equilibrium and prevent subsequent apoptosis in L-02 hepatocytes. These results are compatible with the findings of other studies using CoQ10 against iron-induced neuronal toxicity [28], statin toxicity in hepatocytes [50], or ethanol-induced apoptosis in corneal fibroblasts [51]. …”
Section: Discussionsupporting
confidence: 92%
“…Even if coenzyme Q 10 administration does not relieve myalgia, it may be beneficial due to the fact that CoQ 10 enhances adenosine-5′-triphosphate production, exerts antioxidant activity, influences the expression of multiple genes, has membrane stabilizing properties, protects against LDL oxidation and inhibits proinflammatory cytokines and other factors [ 35 , 80 , 84 , 85 ]. Moreover, it has been suggested that the addition of CoQ 10 to statin therapy may protect hepatocytes from statin-induced injuries and reduce their adverse effects [ 45 , 80 , 86 ].…”
Section: Mechanisms Of Statin Intolerancementioning
confidence: 99%
“…In fact, the depletion of this coenzyme was observed in the liver of our experimental model (Lorza-Gil et al, unpublished data ) as well as in skeletal muscle, heart, brain, plasma, HepG2 and insulin-secreting INS-1 cells after statins treatments ( Tavintharan et al, 2007 ; La Guardia et al, 2013 ; Urbano et al, 2017 ). The second point is that CoQ10 effects are mediated mostly by its free radical scavenger action ( Tavintharan et al, 2007 ; Eghbal et al, 2014 ) rather than by its electron transfer function, since under the present conditions, pravastatin did not inhibit mitochondria respiration. This mechanism was previously proposed by our group ( La Guardia et al, 2013 ; Busanello et al, 2017 ).…”
Section: Discussionmentioning
confidence: 71%